Pharmacy impact on medication reconciliation in the medical intensive care unit - Brittany M Wills; William Darko; Robert Seabury; Luke A Probst; Christopher D Miller; Gregory M Cwikla (Wolters Kluwer Medknow Publications, 2016)
Objective: Pharmacy-driven medication history (MH) programs have been shown to reduce the number of serious or potentially life-threatening (S/PLT) medication discrepancies (MDs) in many settings, but not Intensive Care Units (ICUs). Methods: MHs were repeated over a 6-week period. Demographics, number, and nature of MDs were documented. Discrepancy severity was graded using a previously published method. Primary outcome was the proportion of MHs containing >1 S/PLT MDs. Findings: Sixty-three MHs were repeated. Pharmacy MHs were less likely to contain ≥1 S/PLT MDs (0% vs. 50%, P < 0.001). Conclusion: Pharmacy MHs contained fewer S/PLT MDs in this small sample. S/PLT MDs on admission and home medication lists were common in patients admitted to the medical ICU. Pharmacy-driven medication reconciliation (MR) reduced the number and frequency of these discrepancies. Further research is required to improve current MR procedures.